Lecithostaphylus tylosuri sp. nov. (Digenea, Zoogonidae) from the digestive tract of the needlefish Tylosurus acus imperialis (Teleostei, Belonidae) - Manel, C.; Hela, D.; Lass?d, N. (Acta Parasitologica, 2013)
Lecithostaphylus tylosuri sp. nov. (Digenea, Zoogonidae) specimen were collected from the digestive tract of Tylosurus acus imperialis (Teleostei, Belonidae) caught off the eastern coast of Tunisia. L. tylosuri is very similar to its closest relatives, L. retroflexus and L. nitens. It can be easily distinguished from L. retroflexus (Molin, 1859) in having a more extensive vitellarium, with follicles reaching from the posterior margin of the acetabulum and extending beyond the posterior margin of the testes and a coiled seminal vesicle. L. tylosuri differs from L. nitens as illustrated by Linton 1898, in having a longer cirrus pouch (0.7 mm vs 0.36 mm, respectively) overlapping the anterior edge of the ventral sucker and a submarginal genital pore (submedian in L. nitens). It’s also different from L. nitens as described by Manter 1947 in the vitelline disposition and in having the greater sucker ratio (1: 1.3–2.1 vs 1: 1.3–1.6, respectively). L. tylosuri differs from L. nitens as reported by Machida and Kuramochi 2000 by the absence of variations in the vitellarium disposition in all specimens. L. tylosuri is more similar to L. nitens from group A (considered synonym of L. ahaaha Yamaguti, 1970 = L. nitens by Bray 1987) by having vitelline follicles extending beyond the testes. L. tylosuri can be distinguished from L. ahaaha by its pedunculate rather than prominent acetabulum and its larger body size (4.10–7.85 mm long and 0.75–1.2 mm large vs 2.1–6 mm long and 0.45–1.1 mm large, respectively). The prevalence of L. tylosuri sp. nov. was negatively correlated with host length (decreasing with host size increasing). Host sex does not seem to affect infection parameters.